2015
DOI: 10.1097/der.0000000000000132
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utilization of Repeated Open Application Test Among American Contact Dermatitis Society Members

Abstract: When comparing ROAT clinical and research practice, the majority trend was consistent for leave-on product application frequency and anatomical site, but not for rinse-off product application frequency, or overall duration. Further research is needed to determine best practice recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…A survey of 67 American Contact Dermatitis Society members conducted by Brown et al . in 2015 showed that ROAT was less used as compared to patch testing and that there were variations in methodology with respect to frequency of application, duration of application and the anatomical site preferred for application [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A survey of 67 American Contact Dermatitis Society members conducted by Brown et al . in 2015 showed that ROAT was less used as compared to patch testing and that there were variations in methodology with respect to frequency of application, duration of application and the anatomical site preferred for application [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antigens in the patch test are more concentrated than those in actual use. On the other hand, combinations in actual products might have a synergistic effect in initiating contact allergy [ 1 ]. Repeated open application testing usually only uses one antigen at a time and because of the absence of occlusion, irritant reactions and false positives are avoided.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Irritant or allergic CVAD management products may be identified by a modified open application patch test,32 particularly if the patient is unable to access dermatologic or allergist services 33. The suspected product (eg, antiseptic agent or dressing) is applied to the forearm (contralateral arm to the vascular access device) or thigh and monitored for signs of reaction for 30 to 60 minutes and reassessed in 3 to 4 days for signs of contact dermatitis.…”
Section: Protection Domainmentioning
confidence: 99%
“…Certainly, repeat open application tests are important in confirming or ruling out suspected culprits, and they are commonly used. 6 Data on repeat open application tests performed in NACDG patients, however, are not collected as part of the database, so we cannot provide detailed data on this.…”
mentioning
confidence: 99%